Active learning in Japan: Breaking barriers at individual, institutional, and policy levels. Issue 8 (November 2021) - Ito, Hiroshi; Takeuchi, Shinichi
Active learning has emerged as a means of developing generic employability skills that enable students to prepare for an uncertain future. In this context, many universities have encouraged their instructors to practice active learning. While some scholars indicate challenges with adopting this approach, few empirical studies have examined perceptions of instructors related to its application. This current study addresses this research gap—how instructors perceive the issues regarding the application of active learning—by surveying 157 instructors from across numerous institutions in Japan. Identifying issues at the individual level is important because it can provide guidance for institutional managers and policymakers on the strategies necessary for effective implementation of active learning. While the findings of this study largely confirm those of the extant literature, they also revealed which issues are more pertinent than others. Japanese instructors did not adopt active learning because they were indifferent and reluctant toward active learning and prioritized students' knowledge acquisition over application. We conclude with a discussion of the findings and suggestions to address the perceived issues in implementing active learning at all levels, using the theory of planned behavior.